Methylphenidate-Induced Chorea Due to Possible Cytochrome P450 Metabolism Heterogeneity - A Rare Case. (April 2021) - Jadapalle, Sree Latha Krishna; McCray, Edwin; Masoud, John Azat; Kortz, Michael W.
Abstract: Background: Chorea is defined as a hyperactive movement disorder associated with involuntary, quick, and unpredictable muscle contractions of the limbs, face, and trunk. The unpredictable nature of these movements includes variation in speed, timing, and direction of movement. A wide variety of medications, medical conditions and illicit drugs have been associated with movement disorders. Examples include a multitude of antipsychotic induced movement disorders and dyskinesia related to dopaminergic agents, like levodopa and metoclopramide. Dyskinesias have been associated with psycho-stimulant use, such as methylphenidate. However, most cases reported were associated with large doses or chronic use. Aside from dyskinesia, methylphenidate is known to be associated with tic disorder, tremor, and muscle spasm. However, this case reported is unlike any of the above described and involved the development of chorea after only 2 days of moderate doses of methylphenidate, in a patient on chronic methadone maintenance treatment, with successful arrest of symptoms following discontinuation of the methylphenidate. Case Presentation: A 47-year-old female was admitted to our hospital after presenting to the emergency department with 1 week of violent flailing movements. The ballistic flailing movements started acutely after 2 days of initiating methylphenidate in addition to her chronic methadone treatment and 2-week period of initiation of paroxetine. Lab work showed normal CBC, CMP, CRP, CK, and TSH. Urine drug screen, CT angiography of the head, and Huntington's disease testing were all unremarkable, suggesting a decreased likelihood of illicit drugs, traumatic brain injury, or Huntington's disease etiologies. Confirmation of the diagnosis was made as the chorea symptoms abruptly resolved upon discontinuation of methylphenidate and administration of intravenous Benadryl. The patient has been on methadone alone for 11 months and methylphenidate alone 2 years back with no involuntary movements or any similar presentation that shows the possibility of drug interaction through cytochrome P450 metabolism between Methylphenidate and methadone. Conclusion: We are presenting a rare case report that adds on to the scarce literature on methylphenidate-induced chorea. It also challenges the consulting psychiatrists to broaden their differential diagnosis for acute onset of choreiform movement disorders. This unique case intrigues the thought process to consider the interaction of methylphenidate in the presence of cytochrome P450 2D6 and 3A4 inhibitors like methadone.